Caracterização da ictiofauna de poças de maré em duas praias do nordeste brasileiro utilizando óleo de cravo: quais fatores afetam a distribuição, abundância e diversidade de peixes? - Marques, Jasna Maria Luna (2017)
One of the richest and least studied environments in the coastal zone are the sandstone reefs, where the tide pools are located. In studies that focus on characterization of reef fishes the visual census technique is predominant. However, there are more adequate methodological alternatives for the characterization of resident species, such as the anesthetic eugenol. Thus, the present research aimed to describe the structure of the reef fish assemblage of the Pedra Rachada and Flecheiras beaches, associating with the environmental factors, morphometric aspects of tide pool and anthropogenic impacts in the two localities. An inventory of the resident and cryptic species was made, classifying resident species based on numerical abundance and their occurrence. The samplings were performed in monthly basin, during periods of syzygy low tide, between September 2015 and August 2016, with the use of the anesthetic eugenol in four fixed pools on each beach. Concomitant to the study of the pools was carried out a characterization of the substrate of the pools and an inventory of the environmental impacts along the beach. The sandy substrate was predominant in the Pedra Rachada pools, while the rhodoliths predominated in Flecheiras. The individual’s abundance of Pedra Rachada (158) was higher than Flecheiras (54). Haemulon parra was the most representative species in number of individuals for the two beaches, followed by Haemulon plumieri in Pedra Rachada and Malacoctenus delalandii and Sparisoma radians in Flecheiras. In both beaches the family Labrisomidae predominated in number of species, causing a predominance of resident permanent and cryptic species. The carnivorous trophic category showed the largest number of species in both localities. The two beaches obtained low values of Shannon diversity with averages of 1.14 in Pedra Rachada and 0.88 in Flecheiras. There was a predominance of small individuals in the two beaches. The physical-chemical parameters showed averages of 33ºC of temperature and 38 of salinity. In Pedra Rachada depth was positively associated with diversity and temperature with richness. In Flecheiras the environmental variables did not change the structure of the assembly. The most recurrent environmental impacts were solid waste. However, registered environmental impacts were not able to influence the ecological descriptors of fish assemblage in any of the beaches. The use of clove oil was effective for the accomplishment of this study, contemplating species that are not sampled with the visual census. The large amount of solid waste sampled in this study reveals the need for more studies aimed at this type of impact on the reef species.